Conceptual approaches to the development of the education system in the Republic of Belarus - Karpenko, Igor V. (Journal of the Belarusian State University. Sociology, 2019)
The article is prepared on the basis of the authorʼs report at the Republican Pedagogical Council on 24 August 2017 and presents conceptual approaches and prospects for the development of education in the Republic of Belarus. In the near future, the transition to universal secondary education is expected. It will be a qualitatively new stage in the evolution of the system aimed at raising the educational level of citizens, which will positively affect the development of human potential and the international image of Belarus. Education should be assessed at the level of personal and social development of any person. It is proposed to change the understanding of the final secondary school exam, the mechanism for the entrance examinations, the rules for entering the gymnasium, and to optimize the network of institutions of higher education, taking into account their profile, personnel potential, material and technical base.
Keywords: conceptual approaches to the development of the education system; the national model of multilevel education; the quality of education; profiling of specialities; human resources; educational and scientific production clusters; educational potential of education, social pedagogical and psychological services